Gajah Mada dalam Kaba Bujang Jauh: Struktur dan Relasi-Relasi Tokoh A la Lévi-Strauss - Tienn Immerry (Jurnal Elektronik WACANA ETNIK, 2010)
Sutan Nadal as the main character of this tale became the Prime Minister of Majapahit kingdom in Java. He was known as Gajah Mada. This is interesting to be studied since the origin of Gajah Mada has not been known yet. This Minangkabau classical tale, in Lévi-Strauss structuralism context, should not been put in controversy based on the history and reality. The story, which is believed by certain society and regarded as a true story, could be regarded as a tale by other societies.The sintagmatic relation—relation of characters with others in the story—shows paradigmatic relation—relation of the various characters in the same level. The analysis of the story also found two bundles of relations. They are a bundle of aristocracy relation and a bundle of government relation between Minangkabau and Majapahit kingdom. The analysis of the relation of the characters and bundles of relations reveal the surface structure which shows relations among elements that could be built based on the external characters or empirical characters of the relation, such as family stucture of each characters.The ‘Bujang Jauh’ tale contain the culture of Minangkabau culture which has been extinct. Based on the tale, it is known that a certain society has a whole social system in which all the members have the same tradition and language. Culture is not so simple which is happen instantly. Each society has different culture.